First-Trimester Pyelonephritis Is Associated with Later Initiation of Prenatal Care: A Retrospective Cohort Analysis - McDonnold, Mollie A.; Friedman, Alexander M.; Raker, Christina A.; Anderson, Brenna L. (American Journal of Perinatology, 2012)
We sought to determine the morbidity, frequency, and demographics of pregnant patients with pyelonephritis not yet receiving prenatal care compared with patients with prenatal care. We performed a retrospective cohort analysis of 254 consecutive admissions for pyelonephritis from January 2004 to June 2007 at a single tertiary hospital comparing patients with prenatal care versus patients with no prenatal care. The sample size was adequate to detect a 1-day difference in length of admission between the two groups with an α of 0.05 and 80% power. Categorical variables were compared by Fisher exact test, and continuous variables were compared by the Wilcoxon rank sum or Kruskal-Wallis test. Of the 254 cases, 35 (13.8%) occurred in women who had not established prenatal care. There was no difference in the primary outcome of hospital length of stay. Overall, 29 cases (11.4%) occurred prior to 12 weeks and of these, significantly more patients presented having not established prenatal care (18 versus 11, p < 0.0001). The majority of cases of pyelonephritis that occur prior to 12 weeks are among women with no prenatal care. Although the U.S. Preventative Services Task Force guidelines advise screening urine culture at 12 to 16 weeks, these findings support initiating screening at an earlier gestational age.
Keywords: pyelonephritis; asymptomatic bacteriuria; prenatal care; first trimester screening